Krakatau : the tale of Lampung submerged - Muhammad Saleh; Suryadi, 1965-; McGlynn, John H.; Proudfoot, I. (Ian), 1946-; Hooker, Virgina (Singapore : NUS Press in association with LONTAR, 2014)
Malay classical poem on the eruption of Krakatau in 1883.
'First published in Malay in 1883 under the title Syair Lampung Karam by the printing firm Cap al-Haji Muhammad Tayib in Singapore.'
Includes bibliographical references.
Translated from classical Malay.
Keywords: Volcanoes -- Indonesia -- Poetry; Indonesian poetry -- Translations into English; Krakatoa (Indonesia) -- Poetry